Mapping acceptance: micro scenarios as a dual-perspective approach for assessing public opinion and individual differences in technology perception - Brauner, Philipp (Frontiers in Psychology, 2024)
As technology rapidly evolves, understanding public perception becomes increasingly crucial to aligning research, technology development, and governance. This article introduces micro scenarios as an integrative method for evaluating mental models and social acceptance across numerous technologies and concepts using a few single-item scales within a single comprehensive survey-contrasting with traditional methods that focus on detailed assessments of only one or a few scenarios. The data can be interpreted in two ways: Perspective 1: The average evaluations of each participant can be seen as individual differences, providing reflexive measurements across technologies or topics. This helps in understanding how technology perception relates to other personality factors. Perspective 2: The average evaluations of each technology or topic can be interpreted as technology attributions. This allows for positioning technologies on visuo-spatial maps to identify critical issues, conduct comparative rankings based on selected criteria, and analyze the interplay between different attributions. This dual approach enables the modelling of acceptance-relevant factors that shape public opinion, which is crucial for tailoring technology to better meet human needs. This approach offers a framework for researchers, technology developers, and policymakers to identify pivotal factors for acceptance at both the individual and technology levels. I illustrate this methodology with examples from my research, provide practical guidelines, and include R code to enable others to conduct similar studies. This paper aims to bridge the gap between technological advancement and societal perception, offering a tool for more informed decision-making in technology development and policy-making.